New adaptive hysteresis band width control for direct torque control of induction machine drives - Arkan A. Kadum (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents a new adaptive hysteresis band control approach used in direct torque control (DTC) of the induction motor (IM) drives with the switching tables for the generation of PWM signals. Constant Hysteresis Direct torque control (CHB-DTC) method used the torque and stator flux errors to generate the stator voltage reference and frequency vectors for controlling the three-phase induction motor. The CHB-DTC gives better torque transient performance but it has large steady state ripples. To reduce torque and stator current ripples in CHB-DTC controlled induction motor drives a new adaptive hysteresis band control (AHB) approach is proposed, where the hysteresis band is adapted in real time with the stator flux and torque errors variation, instead of fixed bandwidth. Both classical CHB-DTC method and the proposed adaptive hysteresis band DTC (AHB-DTC) fed three induction motor have been simulated using Matlab/Simulink. The simulation results at different operating conditions over a wide speed range demonstrate the validity, effectiveness, and feasibility of the proposed scheme. The measurements showed that torque ripples were significantly decrease with the new AHB-DTC technique and better speed response in step up or down compared to the CHB-DTC.